Proceedings of the Third International Conference on Sustainable Innovation 2019 – Technology and Engineering (IcoSITE 2019) 2019
DOI: 10.2991/icosite-19.2019.12
|View full text |Cite
|
Sign up to set email alerts
|

Selection Model of Building Demolition Method Based on Expert System

Abstract: Demolition needs special attention because the planning process is complex and has a high risk. In decision making, practitioners face various conditions that influence the choice of demolition methods. This study aims to develop an optimal model for building demolition methods based on the building characteristics. Identification of criteria was conducted in in-depth literature review and interviews with practitioners who have carried out demolition in Indonesia. The five criteria used in this study were stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Anumba et al [12] used an integrated system for demolition technique selection and concluded that the prototype system developed provides users with a clear and structured framework that could improve the decision-making process. Oryza et al [13] utilized the selecting model of building demolition method based on an expert system and concluded that the model can make decisions on the selection of demolition methods with an accuracy of judgment. However, unstructured intuition by demolition engineers based on skill, experience, judgment, or knowledge may sometimes lead to error and inconsistencies, and the AHP utilized in selecting demolition tools are linear dependencies between items of different decision-making levels and not suitable for complex problems which are characterized by dependencies, interactions, and feedback and especially by the dynamic nature of the decision taken.…”
Section: Introductionmentioning
confidence: 99%
“…Anumba et al [12] used an integrated system for demolition technique selection and concluded that the prototype system developed provides users with a clear and structured framework that could improve the decision-making process. Oryza et al [13] utilized the selecting model of building demolition method based on an expert system and concluded that the model can make decisions on the selection of demolition methods with an accuracy of judgment. However, unstructured intuition by demolition engineers based on skill, experience, judgment, or knowledge may sometimes lead to error and inconsistencies, and the AHP utilized in selecting demolition tools are linear dependencies between items of different decision-making levels and not suitable for complex problems which are characterized by dependencies, interactions, and feedback and especially by the dynamic nature of the decision taken.…”
Section: Introductionmentioning
confidence: 99%